Revising moves: writing stories of (re)making - LaVecchia, Christina M., editor; Carr, Allison D., editor; Micciche, Laura R., editor; Rule, Hannah J., editor; Stone, Jayne E. O., editor; Utah State University Press, publisher (Colorado State University. Libraries, 2024)
These meditations on revision by writers in a range of academic genres associated with institutional mundanities, as well as the production of texts, reflect rhetoric and composition as a discipline.--Provided by publisher.
On the page and in our lives / Christina M. LaVecchia, Allison D. Carr, Laura R. Micciche, Hannah J. Rule, and Jayne E. O. Stone -- Revision takes a stand / Hannah J. Rule -- On choosing not to revise / Joseph Harris -- Consulting editor to the rescue: seeing storytelling anew through veteran eyes / Alexandra Hidalgo -- Alejandra chooses life: revising the resignation letter toward counterstory as Epistle / Aja Y. Martinez -- Revision makes space / Christina M. LaVecchia -- Revising a cover letter, revising a life: bridging professional identities / Ellery Sills and Fernando Sánchez -- Re-visioning letters of recommendation / Cameron Becker, Kelly Blewett, and Vanessa Kraemer Sohan -- Creating and holding space as revision in WPA lives / Christy I. Wenger -- Revision approaches feedback / Laura R. Micciche -- On the slippages and swells of revising digital media / Rich Shivener -- "AnotherDraft.docx": the role of horizontal mentoring in publishing as graduate students / Dana Comi and Alisa Russell -- Revising scholarly peer review: don't be a dick / Raúl Sánchez -- Revision as protecting what is important / Cruz Medina -- Revision meets the world / Allison D. Carr -- Revising an antiracism statement for known and unknown audiences / Mike Garcia -- Feeling our way through collaborative revision when the world is on fire / Collie Fulford and Stefanie Frigo -- Whose exigence? The social dynamics of a writing across the curriculum plan-in-process / Christopher Basgier -- Revision spirals / Jayne E. O. Stone -- Definition as invention: turning a familiar concept into a critical keyword / William Duffy -- Uncovering the veil: revising the dichotomy between motherhood and academic personas / Jule Wallis-Thomas -- "That's where it sleeps": what I say when I point to my abandoned project / Karen R. Tellez-Trujillo -- Drawing a blank: illustrating the revision process / Ian Golding -- Losses, leavings, remakings: an afterword / Jessica Restaino.
Keywords: English language -- Rhetoric; Editing; Academic writing; Report writing